Hailing the divine: Inducement motifs in the psalms and Levantine inscriptions. (June 2019) - Sumner, Stephen T
The psalms employ various motifs to induce divine favor, the principal categories of which are praise, protest, and piety. The inducing quality of these rhetorical devices is most easily discerned in petitionary contexts, where their implementation increased the efficacy of the petition. These exhibit considerable overlap with those attested in the ancient Levantine inscriptions, helping us discern the religious utility of the motifs. More importantly, the same motifs that occur in the 77 psalms of petition also appear with regularity in the 73 psalms that lack one. Considering the religious and literary matrix of psalmic production, the evidence suggests that, where these inducement motifs were employed, they sought to obtain divine favor, even in the absence of a petition.